1996
DOI: 10.1016/0014-5793(96)00886-1
|View full text |Cite
|
Sign up to set email alerts
|

High‐level expression of Pinus sylvestris glutamine synthetase in Escherichia coli

Abstract: protein showed the same molecular size as a native Scots pine GS subunit. Antibodies against the pET3c-GSPll4 encoded protein were raised in rabbits by injecting purified preparations and specificity was determined by immunoprecipitation of GS activity present in pine crude extracts. In spite of the antibodies were able to recognize both cytosolic and chloroplastic GS in tomato plants, they were unable to immunodetect chloroplastic GS in green cotyledons of pine seedlings and cytosolic GS was the unique recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 31 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…Tissue sectioning, fixation, and embedding were conducted as described by Canales et al (2011b). AS and GS protein were revealed using specific antibodies (Cantón et al, 1996; Cañas et al, 2006). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue sectioning, fixation, and embedding were conducted as described by Canales et al (2011b). AS and GS protein were revealed using specific antibodies (Cantón et al, 1996; Cañas et al, 2006). …”
Section: Methodsmentioning
confidence: 99%
“…(B) Immunohistochemical localization. Sections of hypocotyls were probed with AS (Cañas et al, 2006) and GS (Cantón et al, 1996) antibodies. Control sections were processed in parallel in the absence of immunoprobes.
Figure A2 Alignment of the deduced amino acid sequences of PtMYB1 and PpMYB1 full-length cDNAs .
…”
Section: Figure A1mentioning
confidence: 99%
“…Western-blot analysis SDS-PAGE and electroblotting were carried out as described elsewhere (Cantón et al 1996). The membranes were blocked for 1 h with 3% (w/v) BSA dissolved in TPBS: 1X PBS (140 mM NaCl, 3 mM KCl, 5 mM Na 2 HPO 4 , 1.47 mM KH 2 PO 4 , pH 7.4), 0.05% (v/ v) Tween-20, and incubated overnight at room temperature with 0.95 g of puriWed anti-ASPG antibodies diluted in TPBS with 0.05% (w/v) BSA.…”
Section: Antibody Productionmentioning
confidence: 99%
“…Total proteins were extracted from needles and vascular tissue of Pinus pinaster separated by 2D PAGE and revealed by silver staining [30]. Alternatively, 2D gels were electrotransferred to nitrocellulose filters and the GS spots immunodetected using specific antibodies [18]. In situ proteolytic digestion of GS spots, peptide purification and microsequencing analysis were performed following the method of Costa et al [31].…”
Section: Methodsmentioning
confidence: 99%
“…We have previously characterized a GS1 cDNA clone from Scots pine [17] and showed that it encodes the predominant GS polypeptide in green tissues [18]. This gene is actively expressed in pine cotyledons in a light‐dependent fashion [19] suggesting a specific role in glutamine biosynthesis and ammonium assimilation associated with chloroplast activity.…”
Section: Introductionmentioning
confidence: 99%